Diagnosis of Alzheimer's disease before dementia: A study of UK psychiatrists. (31st December 2021) - Walpert, Madeleine; Mitchell, Susan; Bamford, Claire; Ivenso, Chineze; McKirdy, Stuart; Pattan, Vivek; Rodda, Joanne; Sikdar, Sudip; Barber, Robert
Abstract: Background: Alzheimer's disease (AD) is increasingly conceptualised as a continuum spanning presymptomatic, symptomatic pre‐dementia and dementia stages. With potential disease modifying treatments emerging, this study explored the views of clinicians working in Old Age Psychiatry in the UK regarding the diagnosis of symptomatic AD before dementia, including the role of biomarkers, and the preparedness of services to deliver future disease modifying treatments. Method: This study, conducted by the Royal College of Psychiatrists and Alzheimer's Research UK, used a two‐stage quantitative and qualitative approach consisting of an online survey (n=493) followed by focus groups (n=42) of clinicians. Result: Conceptualising AD as a continuum was considered a helpful framework for thinking about disease pathology, progression and treatment. However, translating this framework into clinical practice generated a number of challenges including uncertainties about diagnostic nomenclature and criteria with at least seven diagnostic terms possible. Overall, terms referencing "mild cognitive impairment" were considered more helpful than those explicitly stating AD. Hesitancy to reference AD at this stage was influenced by concerns about the accuracy of diagnostic criteria, limitations linked to biomarkers and potential negative impacts on individuals, especially in the absence of disease modifying treatments. Access to biomarkers other than CT was sub‐optimal, 96% of responders reported insufficient or no access to CSF and 93% to PET Aβ, limited access negatively impacted on the clinician's confidence in their utility (P<0.001). Psychiatrists indicated that it was important their services offer disease modifying treatments if licensed but recognised that services faced significant challenges to be prepared, including capacity, resources and staff expertise. Conclusion: Diagnosing AD before the onset of dementia is likely to become increasingly relevant if new treatments are licensed, but this study highlights a number of important challenges to achieve this including concerns about the reliability and validity of the diagnostic criteria and access to key biomarkers. There was a clear view that Old Age Psychiatry services should be able to provide any future treatments alongside their usual care but recognition that this would require better access to biomarkers, clearer diagnostic criteria, up‐skilling of staff and changes to training as well as changes to care pathways.